A Research on the Biophilic Concept upon School’s Design from Hot Climate: A Case Study from Iraq - Amjad Almusaed; Asaad Alasadi; Asaad Almssad (Advances in Materials Science and Engineering)
In recent years, there have been solid global trends and severe attempts by ministries of education in the world to improve the reality of educational institutions and schools through the design and construction of schools and educational systems that meet the requirements of the age by applying the concepts of sustainable and effective systems to the new generation. They called for a promising future and hence the need to activate the applications of the biophilic schools. The theme of the biophilic schools is closely related to the concept of sustainable environmental structures that deal with the surrounding natural environment with intimacy, which is one of the most important new methods of design and construction at present, where ecological challenges are powerfully evoked in the making of their design decisions. Biophilic schools are an essential part of a new concept that wants to design revolutionary educational systems with new economic outputs that are valuable but do not depart from the idea of sustainable schools in general. It represents an expression given to schools designed to be environmentally sensitive and healthy for their occupants and educational systems based on experience, humanity, and attraction. Indeed, many architects have begun to explore and develop new architectural designs linked with the concepts of biophilic schools. Through the researchers’ awareness of the negative circumstance experienced by school buildings in Iraq and by investing in the recommendations of an applied field research, it was reached to crystallize the research problem represented in the obstacles that schools suffer from, which calls for the search for developmental solutions for an efficient educational environment, and in order to reach this goal, by informing researchers about new global experiences in this field, the research presented its hypothesis in choosing the model of biophilic schools that exist in many countries in the world, because of what it can provide from successful and fruitful educational and urban components. The researchers reached many conclusions and recommendations aimed at applying the research hypothesis and achieving its goals.